PENGARUH TEKNIK PIJAT AKUPRESUR TERHADAP PENURUNAN INTENSITAS NYERI PADA KALA I FASE AKTIF PERSALINAN DI PUSKESMAS KORBAFO TAHUN 2022 - Vitrilina - Hutabarat; Kristin Natalia (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Labor pain is a physiological thing experienced by every mother giving birth. Pain arises from uterine contractions, cervical dilatation and stretching of the birth canal. As the frequency of uterine contractions increases, the pain becomes more intense. If pain is not overcome, it can affect the psychology of the mother in childbirth, namely fear and anxiety. Fear and anxiety have a negative effect on childbirth which can affect the health condition of the mother and fetus. Research on the effect of acupressure massage techniques on reducing pain intensity in the first stage of the active phase of labor was conducted at the Korbafo Puskesmas. This research uses quantitative analytic research with a Quasi Experimental design with a one group pre-test and post-test with control research design. Data collection uses an observation sheet. Acupressure massage is done by pressing on the SP 6 (bilateral) point for 30 times the pressure and BL 32 (bilateral) for 30 times the pressure. The number of samples in this study were 10 mothers who gave birth. The sampling technique used was purposive sampling. The data analysis used is the Wilcoxon test. The results of this study indicate that the majority of respondents before acupressure experienced severe pain, as many as 9 people (90%). The majority of respondents after acupressure experienced mild pain as many as 6 people (60%), ie with a p value = 0.004 (p = <0.05) which means that there is an influence of acupressure massage techniques on reducing labor pain. It is recommended that midwives can apply this as a non-pharmacological alternative that has minimal side effects in reducing labor pain.